Sugar migration induced by the Wagner-Meerwein rearrangement of 28-O-glycosyl-betulin derivatives. Issue 13 (30th March 2017) - Korda, Anna; Pakulski, Zbigniew; Cmoch, Piotr; Gwardiak, Katarzyna; Karczewski, Romuald
Abstract: Treatment of betulin-type saponins, in which the sugar moiety is connected at the 28-position, with TMSOTf affords 3-O-substituted allobetulin saponins. This unprecedented migration of the sugar part is driven by the Wagner-Meerwein rearrangement of the betulin core. According to our mechanistic studies an oxocarbenium ion released during the rearrangement reacts with the free 3-OH group of the triterpene affording the final allobetulin saponin. Migration rate depends on the size and configuration of the sugar moiety. Graphical abstract: